Development and Characterization of Pepducins as Gs-biased Allosteric Agonists - Carr, Richard; Du, Yang; Quoyer, Julie; Panettieri, Reynold A.; Janz, Jay M.; Bouvier, Michel; Kobilka, Brian K.; Benovic, Jeffrey L. (The Journal of biological chemistry, 2014)
The β2-adrenergic receptor (β2AR) is a prototypical G protein-coupled receptor that mediates many hormonal responses, including cardiovascular and pulmonary function. β-Agonists used to combat hypercontractility in airway smooth muscle stimulate β2AR-dependent cAMP production that ultimately promotes airway relaxation. Chronic stimulation of the β2AR by long acting β-agonists used in the treatment of asthma can promote attenuated responsiveness to agonists and an increased frequency of fatal asthmatic attacks. β2AR desensitization to β-agonists is primarily mediated by G protein-coupled receptor kinases and β-arrestins that attenuate receptor-Gs coupling and promote β2AR internalization and degradation. A biased agonist that can selectively stimulate Gs signaling without promoting receptor interaction with G protein-coupled receptor kinases and β-arrestins should serve as an advantageous asthma therapeutic. To identify such molecules, we screened ∼50 lipidated peptides derived from the intracellular loops of the β2AR, known as pepducins. This screen revealed two classes of Gs-biased pepducins, receptor-independent and receptor-dependent, as well as several β-arrestin-biased pepducins. The receptor-independent Gs-biased pepducins operate by directly stimulating G protein activation. In contrast, receptor-dependent Gs-biased pepducins appear to stabilize a Gs-biased conformation of the β2AR that couples to Gs but does not undergo G protein-coupled receptor kinase-mediated phosphorylation or β-arrestin-mediated internalization. Functional studies in primary human airway smooth muscle cells demonstrate that Gs-biased pepducins are not subject to conventional desensitization and thus may be good candidates for the development of next generation asthma therapeutics. Our study reports the first Gs-biased activator of the β2AR and provides valuable tools for the study of β2AR function.A Gs-biased agonist for the β2-adrenergic receptor (β2AR) has yet to be reported. A screen of β2AR pepducins identified receptor-dependent and receptor-independent pepducins that selectively activate Gs. Receptor-dependent pepducins promote a Gs-biased conformation of the β2AR, whereas receptor-independent pepducins directly activate Gs. Gs-biased pepducins provide a valuable tool for the continued study of β2AR function and may prove useful as next-generation asthma therapeutics.